In Vitro Control Of Five Pathogenic Fungi Isolated From Groundnut (Arachis Hypogaea L.) - Sharmin, Shaila; Shamsi, Shamim (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Efficacy of five plant extracts namely, Allium cepa, Allium sativum, Azadirachta indica, Tagetes patula and Zingiber officinale was evaluated against five pathogenic species of fungi isolated from groundnut in vitro. These were Colletotrichum acutatum, Colletotrichum dematium, Colletotrichum orbiculare, Colletotrichum sp. and Fusarium semitectum. Colony growth of C. dematium was completely checked with Allium sativum at all the concentrations used (5, 10 and 20 %). Similarly A. cepa, A. sativum and A. indica completely inhibited the colony growth of C. orbiculare at the same concentrations used. T. patula and Z. officinale also showed appreciable inhibition in colony growth of five species of fungi at 10 and 20% concentrations. J. Asiat. Soc. Bangladesh, Sci. 39(1): 27-33, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16030